Jones Day Foundation gifts USD 1 million to SMU - Singapore Management University (Institutional Knowledge at Singapore Management University, 2021)
Singapore Management University (SMU) today announced that it has received a gift of USD1 million (approximately S$1.3 million) from the Jones Day Foundation to fund the Jones Day LLM (Judicial Studies) Scholarships and the Jones Day Top Scholar Award.